Flood and Dengue: Increased risk of Gestational Pestilences - Rizwan, Amna; Tariq, Moeez; Imran, Maryum (Journal of the Pakistan Medical Association, 2023)
Madam Editor, Dengue fever is an acute viral disease caused by an RNA (Ribonucleic Acid) virus transmitted by Aedes mosquitoes. Symptoms can range from asymptomatic fever to life-threatening complications such as haemorrhagic fever and shock (1). Dengue fever is recognized by the (WHO (World Health Organization)) World Health Organization as a serious global public health threat in tropical and subtropical countries. Dengue-endemic regions are home to 2.5 billion people, and 400 million infections occur each year, with mortality rates exceeding 20% in some areas (2). Extremely heavy rains have lately devastated Pakistan, with its most populous metropolis of Karachi witnessing the worst floods in a century. Flooding and inadequate water sanitation have increased the risk of dengue, malaria, and other water-borne disease outbreaks. Determining whether dengue infection during pregnancy is associated with adverse effects on the fetus is important, given that women of reproductive age in dengue-endemic areas are at risk of contracting the disease. Studies have suggested an association between maternal infection during pregnancy and preterm birth, low birth weight, small gestational age births, stillbirth, and miscarriage (3, 4). According to Pouliot SH, et al., high rates of cesarean deliveries (44%) and pre-eclampsia (12%) occurred in women who had dengue infection during pregnancy (5). Even though there are several variants of dengue infection, the study found that the proportion of DENV-4 in pregnant women was higher than in non-pregnant women (6), the reason for which is still unclear. The gestational period involves various anatomical and physiological changes in the female body, such as increased capillary permeability, hemodilution, leukocytosis, thrombocytopenia, etc., which may complicate the assessment of the clinical manifestation of dengue due to opposing effects on the body, such as the contradicting leucocyte concentration, as pregnancy causes leukocytosis, whereas dengue causes leukopenia (6). Though the exact mechanism of the effect of maternal dengue on the fetus is yet to be determined, recent studies have put forward two mechanisms for fetal and neonatal morbidity caused by maternal dengue infection. The first theory is that dengue infection causes hemodynamic changes during pregnancy that could affect the placenta and cause fetal hypoxia, In contrast, the second theory states that dengue infection affects the fetus directly (7). —Continue